Extranodal Natural Killer/T-Cell Lymphoma Masquerading as Chronic Rhinosinusitis in a Native American Man - Kendra D. Marr; Biagio J. Collura; Rebecca Wig; Dory Arevalo Salazar; Robert Kim (Annals of Internal Medicine: Clinical Cases)
Extranodal natural killer/T-cell lymphoma (ENKTCL) is a rare Epstein-Barr virus–associated malignancy arising from natural killer cells in nonlymphoid tissues, primarily the upper aerodigestive mucosa. It is rare in the United States but is most frequently seen among the Hispanic population. Clinically, ENKTCL often manifests with nonspecific nasopharyngeal symptoms resembling chronic rhinosinusitis (CRS), making it difficult to diagnose. The absence of standard therapy results in challenging therapeutic decisions and poor outcomes. We report a case of ENKTCL in a 67-year-old Native American, non-Hispanic man with a history of relapsing-remitting CRS.